A Survey of Operating Systems Infrastructure for Embedded Systems - Friedrich, Luis (2009)
Since early applications in the 1960s, embedded systems have come down in price and there has been a dramatic rise in processing power and functionality. In addition, embedded systems are becoming increasingly complex. High-end devices, such as mobile phones, PDAs, entertainment devices, and set-top boxes, feature millions of lines of code with varying degrees of assurance of correctness. Nowadays, more and more embedded systems are implemented in a distributed way, a wide range of high-performance distributed embedded systems have been designed and deployed. As a lot of aspects of embedded system design become increasingly dependent on the effective interaction of distributed processors, it is clear that as much effort needs to be focused on software infrastructure, such as operating systems, with respect to how to provide functionality in order to fulfill these requirements. This technical report presents some of the approaches associated to operating systems that have been used in order to fulfill these needs.